A composite bipolar plate for all-vanadium liquid flow battery and a preparation method thereof

By using epoxy resin matrix, graphite felt conductive main network and nanocarbon material conductive secondary network in the all-vanadium liquid flow battery bipolar plate, and introducing hyperbranched polyethylene copolymer, the problem of difficult to take into account both the conductivity and mechanical strength of the bipolar plate is solved, and the battery efficiency and energy efficiency are improved.

CN118943405BActive Publication Date: 2025-03-18HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411414032.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-18
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing all-vanadium flow battery bipolar plates are difficult to take into account high conductivity and high mechanical strength, resulting in low battery efficiency and energy efficiency.

Method used

Epoxy resin is used as the matrix, graphite felt as the three-dimensional conductive main network, and nanocarbon material as the conductive subnet. By introducing hyperbranched polyethylene copolymers containing epoxy groups at the end, the compatibility and dispersion of the nanocarbon material and the epoxy resin are enhanced, and composite bipolar plates with high conductivity and high mechanical strength are prepared.

Benefits of technology

The conductivity and mechanical properties of the composite bipolar plate are achieved while improving the voltage efficiency and energy efficiency of the all-vana flow battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118943405B_ABST
    Figure CN118943405B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of bipolar plates for all-vanadium liquid flow batteries, and discloses a composite bipolar plate for an all-vanadium liquid flow battery and a preparation method thereof. The composite bipolar plate is used as a matrix, a graphite felt is used as a three-dimensional conductive main network, and a nano-carbon material is used as a conductive secondary network to provide more conductive paths for the graphite felt. A hyperbranched polyethylene copolymer containing an epoxy group at the end is synthesized by a one-pot method, and the nano-carbon material is obtained by auxiliary stripping. Meanwhile, the nano-carbon material is modified by a CH-π non-covalent force to prevent the nano-carbon material from agglomerating. The terminal epoxy group can enhance the compatibility of the nano-carbon material with the epoxy resin matrix, and improve the dispersion uniformity of the nano-carbon material in the matrix, so that the conductivity and mechanical strength of the composite bipolar plate are improved at the same time, and the voltage efficiency and energy efficiency of the all-vanadium liquid flow battery are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bipolar plates for all-vanadium liquid flow batteries, and in particular relates to a composite bipolar plate for an all-vanadium liquid flow battery and a preparation method thereof. Background Art

[0002] With the increasing shortage of non-renewable energy, the development of renewable energy has attracted people's attention. However, it is usually intermittent and volatile, which makes the energy supply of renewable energy unsustainable for a long time. In order to cope with the continuous energy supply during the day or even between seasons, new long-term distributed energy storage systems represented by flow batteries have gradually developed to meet and expand the energy storage needs in different scenarios. All-vanadium liquid flow batteries use a single vanadium element as the active substance of the electrolyte, which can better avoid the problem of cross-contamination of positive and negative electrolytes, and have become the most mature liquid flow battery technology currently in industrialization.

[0003] As one of the key materials of all-vanadium liquid flow batteries, bipolar plates play the role of isolating positive and negative electrolytes and preventing electrolytes from corroding current collectors. Their own impedance is one of the main factors affecting the ohmic polarization of all-vanadium liquid flow batteries. According to their working scenarios, bipolar plates need to have the following characteristics: i. Good conductivity, reducing resistance voltage division and improving battery efficiency; ii. Corrosion resistance, preventing electrolyte corrosion, causing leakage or corrosion of current collectors; iii. Electrochemical stability, preventing the bipolar plates from undergoing charge and discharge redox reactions that affect performance; iv. Good strength and toughness, on the one hand, preventing the bipolar plates from being too soft and blocking the electrolyte flow channel, and on the other hand, preventing the bipolar plates from being brittle when stacked and tightened to make the battery stack. However, the above performance is often difficult to take into account. Taking the commonly used bipolar plates - metal bipolar plates, graphite bipolar plates and carbon-plastic composite bipolar plates as examples, metal bipolar plates have excellent conductivity and mechanical properties, but are prone to electrochemical corrosion when in contact with strong acid solutions of vanadium ions; graphite bipolar plates have excellent conductivity and corrosion resistance, but have low strength and complex processing technology.

[0004] Carbon-plastic composite bipolar plates combine the advantages of high conductivity and corrosion resistance of carbon materials and high mechanical properties and easy processing of resins. However, compared with metal and graphite bipolar plates, their conductivity is still at a relatively low level. To further improve their conductivity, it is usually necessary to increase the content of conductive carbon materials and reduce the content of resins. However, the low resin content cannot provide sufficient strength, and the bonding is insufficient during processing, so it cannot be formed. Therefore, there is a contradiction between improving both conductivity and mechanical properties. Therefore, the development of a composite bipolar plate with high conductivity and high mechanical strength and its preparation method has become a problem that needs to be solved at present. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a composite bipolar plate for an all-vanadium liquid flow battery and a preparation method thereof, which takes epoxy resin as a matrix, introduces graphite felt as a conductive main network, and carbon material as a conductive secondary network, so as to obtain a composite bipolar plate with both high conductivity and high mechanical strength at a lower carbon material content.

[0006] The present invention adopts the following technical solution:

[0007] A method for preparing a composite bipolar plate for an all-vanadium liquid flow battery comprises the following steps:

[0008] S1: dehydrate and deoxygenate the reaction bottle, and under the protection of ethylene, add 50 parts by mass of anhydrous solvent, 4-6 parts by mass of epoxy-containing acrylic monomer, and 0.2-0.5 parts by mass of palladium catalyst into the reaction bottle in sequence, stir and dissolve, adjust the ethylene pressure to 0.1-1 MPa, react at 25°C for 12-24 hours, and after the reaction is completed, stop the ethylene supply, blow cold wind to remove the anhydrous solvent, obtain a saturated preliminary product, and obtain a hyperbranched polyethylene copolymer containing epoxy groups after separation and purification;

[0009] S2: adding 2-6 parts by weight of carbon material and 1-4 parts by weight of hyperbranched polyethylene copolymer containing epoxy groups to 750 parts by weight of solvent, ball milling for 24-72 hours to obtain a mixed solution, centrifuging the mixed solution, filtering the supernatant to obtain a filter cake, repeatedly eluting the filter cake with a solvent, and drying to obtain a nano-carbon material;

[0010] S3: Take 0.75-4.5 parts by mass of nanocarbon material, add it to 15 parts by mass of solvent, and ultrasonicate it to obtain a dispersion liquid. Add the dispersion liquid to 30 parts by mass of epoxy resin, stir for 1-2 hours, and ultrasonicate it for 0.5-2 hours. Then, add 30 parts by mass of curing agent, and stir for 30 minutes to obtain a composite liquid.

[0011] S4: Coat the composite liquid onto the surface of 30 parts by mass of graphite felt, put it into an oven for pre-curing, immerse the graphite felt into the plugging liquid after pre-curing and take it out, cover both sides of the graphite felt with carbon paper, put it into a mold and perform hot pressing and curing, and obtain a composite bipolar plate after curing.

[0012] Preferably, in step S1, the anhydrous solvent includes at least one of dichloromethane, chloroform, toluene and chlorobenzene.

[0013] Preferably, in step S1, the epoxy-containing acrylic monomer includes at least one of 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, glycidyl acrylate, and glycidyl methacrylate.

[0014] Preferably, in step S2, the carbon material includes at least one of graphite and multi-walled carbon nanotubes.

[0015] Preferably, in steps S2 and S3, the solvent includes at least one of chloroform, tetrahydrofuran, N,N-dimethylformamide, cyclohexanone and toluene.

[0016] Preferably, in step S2, the drying temperature is 40-60° C., and the drying time is 6-12 hours.

[0017] Preferably, in step S4, the pre-curing temperature is 40-60° C., and the pre-curing time is 1-2 hours.

[0018] Preferably, in step S4, the hot pressing temperature is 100-120° C., and the hot pressing time is 0.5-2 h.

[0019] A composite bipolar plate for an all-vanadium liquid flow battery is prepared by using the above-mentioned method for preparing a composite bipolar plate for an all-vanadium liquid flow battery.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention uses a synthesized hyperbranched polyethylene copolymer containing an epoxy group at the end to assist in stripping to obtain a nano-carbon material. The hyperbranched polyethylene copolymer has a CH-π interaction with the nano-carbon material, and non-covalently modifies the nano-carbon material to prevent the nano-carbon material from agglomerating. At the same time, the terminal epoxy group can enhance the compatibility of the nano-carbon material with the epoxy resin matrix and improve the dispersion uniformity of the nano-carbon material in the matrix, thereby improving the conductivity and mechanical strength of the composite bipolar plate at the same time, thereby achieving an increase in the voltage efficiency and energy efficiency of the all-vanadium liquid flow battery.

[0022] 2. The present invention uses the excellent three-dimensional conductive network structure of graphite felt itself as the conductive path. The graphite felt contains abundant voids, which can be filled into the epoxy resin matrix to form a mechanically reinforced skeleton, thereby better maintaining the continuity of the conductive path and the mechanically reinforced skeleton. At the same time, by introducing nano-carbon materials to further overlap and improve the three-dimensional conductive network, at a lower content of nano-carbon materials, the composite bipolar plate has both high conductivity and mechanical strength, thereby improving the voltage efficiency and energy efficiency of the all-vanadium liquid flow battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 1 is a comparison chart of the resistivity of the composite bipolar plates prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 and 3;

[0024] Figure 2 It is a comparison chart of the tensile strength of the composite bipolar plates prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the present invention are not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1: The composite bipolar plate of this example is prepared by the following steps:

[0027] S1: Dehydrate and deoxygenate the reaction bottle. Under ethylene protection, add 50g of anhydrous dichloromethane, 4g of methacrylate epoxypropene monomer, and 0.5g of palladium catalyst into the reaction bottle in sequence, stir and dissolve, adjust the ethylene pressure to 0.1MPa, and react at 25°C for 24h. After the reaction is completed, stop the ethylene supply, blow cold wind to remove the anhydrous dichloromethane, and obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene copolymer containing epoxy groups is obtained;

[0028] S2: 2 g of multi-walled carbon nanotubes and 1 g of a hyperbranched polyethylene copolymer containing epoxy groups were added to 750 g of chloroform, and ball-milled for 48 h to obtain a mixed solution. After the mixed solution was centrifuged, the supernatant was filtered to obtain a filter cake, and the filter cake was repeatedly rinsed with chloroform, and then dried to obtain carbon nanotubes;

[0029] S3: Take 0.75g of carbon nanotubes, add 15g of chloroform, and ultrasonicate to obtain a dispersion, add the dispersion to 30g of epoxy resin, stir for 1h, ultrasonicate for 0.5h, then add 30g of curing agent, and stir for 30min to obtain a composite solution;

[0030] S4: Coat the composite liquid onto the surface of 30g of graphite felt, put it into an oven for pre-curing at 60°C for 1h, immerse the graphite felt in the plugging liquid after pre-curing and take it out, cover carbon paper on both sides of the graphite felt, put it into a mold and perform hot pressing curing at a temperature of 100°C and a time of 0.5h to obtain a composite bipolar plate after curing.

[0031] Example 2: The composite bipolar plate of this example is prepared by the following steps:

[0032] S1: Dehydrate and deoxygenate the reaction bottle. Under ethylene protection, add 50g of anhydrous chloroform, 5g of glycidyl acrylate monomer, and 0.2g of palladium catalyst into the reaction bottle in sequence, stir and dissolve, adjust the ethylene pressure to 0.5MPa, and react at 25°C for 12h. After the reaction is completed, stop the ethylene supply, blow cold wind to remove the anhydrous chloroform, and obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene copolymer containing epoxy groups is obtained;

[0033] S2: 4 g of multi-walled carbon nanotubes and 2 g of hyperbranched polyethylene copolymer containing epoxy groups were added to 750 g of tetrahydrofuran, and ball-milled for 24 h to obtain a mixed solution. After the mixed solution was centrifuged, the supernatant was filtered to obtain a filter cake, and the filter cake was repeatedly rinsed with tetrahydrofuran, and then dried to obtain carbon nanotubes;

[0034] S3: Take 1.5g of carbon nanotubes, add them to 15g of tetrahydrofuran, and ultrasonicate to obtain a dispersion, add the dispersion to 30g of epoxy resin, stir for 1.5h, ultrasonicate for 1h, then add 30g of curing agent, and stir for 30min to obtain a composite solution;

[0035] S4: Coat the composite liquid onto the surface of 30g of graphite felt, put it into an oven at 40°C for pre-curing for 2h, immerse the graphite felt in the plugging liquid after pre-curing and take it out, cover carbon paper on both sides of the graphite felt, put it into a mold and perform hot pressing curing at a temperature of 110°C and a time of 1h to obtain a composite bipolar plate after curing.

[0036] Example 3: The composite bipolar plate of this example is prepared by the following steps:

[0037] S1: Dehydrate and deoxygenate the reaction bottle. Under ethylene protection, add 50g of anhydrous dichloromethane, 6g of 1,2-epoxy-9-decene monomer, and 0.4g of palladium catalyst into the reaction bottle in sequence, stir and dissolve, adjust the ethylene pressure to 1MPa, and react at 25°C for 20h. After the reaction is completed, stop the ethylene supply, blow cold wind to remove the anhydrous dichloromethane, and obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene copolymer containing epoxy groups is obtained;

[0038] S2: 6 g of multi-walled carbon nanotubes and 4 g of hyperbranched polyethylene copolymer containing epoxy groups were added to 750 g of N,N-dimethylformamide, and ball-milled for 72 h to obtain a mixed solution. After the mixed solution was centrifuged, the supernatant was filtered to obtain a filter cake, and the filter cake was repeatedly rinsed with N,N-dimethylformamide, and then dried to obtain carbon nanotubes;

[0039] S3: Take 3g of carbon nanotubes, add 15g of N,N-dimethylformamide and ultrasonically obtain a dispersion, add the dispersion to 30g of epoxy resin, stir for 2h, ultrasonically for 2h, then add 30g of curing agent, stir for 30min to obtain a composite solution;

[0040] S4: Coat the composite liquid onto the surface of 30g of graphite felt, put it into an oven for pre-curing at 50°C for 1.5h, immerse the graphite felt in the plugging liquid after pre-curing and take it out, cover both sides of the graphite felt with carbon paper, put it into a mold and perform hot pressing curing at a temperature of 120°C for 2h to obtain a composite bipolar plate after curing.

[0041] Example 4: The composite bipolar plate of this example is prepared by the following steps:

[0042] S1: Dehydrate and deoxygenate the reaction bottle. Under ethylene protection, add 50g of anhydrous dichloromethane, 6g of 1,2-epoxy-7-octene monomer, and 0.4g of palladium catalyst into the reaction bottle in sequence, stir and dissolve, adjust the ethylene pressure to 0.1MPa, and react at 25°C for 24h. After the reaction is completed, stop the ethylene supply, blow cold wind to remove the anhydrous dichloromethane, and obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene copolymer containing epoxy groups is obtained;

[0043] S2: 4 g of multi-walled carbon nanotubes and 4 g of hyperbranched polyethylene copolymer containing epoxy groups were added to 750 g of N,N-dimethylformamide, and ball-milled for 48 h to obtain a mixed solution. After the mixed solution was centrifuged, the supernatant was filtered to obtain a filter cake, and the filter cake was repeatedly rinsed with N,N-dimethylformamide, and then dried to obtain carbon nanotubes;

[0044] S3: Take 4.5g of carbon nanotubes, add them to 15g of N,N-dimethylformamide and ultrasonically obtain a dispersion, add the dispersion to 30g of epoxy resin, stir for 2h, ultrasonically for 2h, then add 30g of curing agent, stir for 30min to obtain a composite solution;

[0045] S4: Coat the composite liquid onto the surface of 30g of graphite felt, put it into an oven for pre-curing at 60°C for 1h, immerse the graphite felt in the plugging liquid after pre-curing and take it out, cover both sides of the graphite felt with carbon paper, put it into a mold and perform hot pressing curing at a temperature of 120°C for 1h, and obtain a composite bipolar plate after curing.

[0046] Example 5: The composite bipolar plate of this example is prepared by the following steps:

[0047] S1: Dehydrate and deoxygenate the reaction bottle. Under ethylene protection, add 50g of anhydrous toluene, 6g of 1,2-epoxy-5-hexene monomer, and 0.4g of palladium catalyst into the reaction bottle in sequence, stir and dissolve, adjust the ethylene pressure to 0.1MPa, and react at 25°C for 24h. After the reaction is completed, stop the ethylene supply, blow cold wind to remove the anhydrous toluene, and obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene copolymer containing epoxy groups is obtained;

[0048] S2: 4 g of graphite and 4 g of a hyperbranched polyethylene copolymer containing epoxy groups were added to 750 g of toluene, and ball-milled for 48 h to obtain a mixed solution. After the mixed solution was centrifuged, the supernatant was filtered to obtain a filter cake, and the filter cake was repeatedly rinsed with toluene, and graphene was obtained after drying;

[0049] S3: Take 0.75g of graphene, add it to 15g of toluene and ultrasonicate to obtain a dispersion, add the dispersion to 30g of epoxy resin, stir for 2h, ultrasonicate for 2h, then add 30g of curing agent, stir for 30min to obtain a composite liquid;

[0050] S4: Coat the composite liquid onto the surface of 30g of graphite felt, put it into an oven for pre-curing at 60°C for 1h, immerse the graphite felt in the plugging liquid after pre-curing and take it out, cover both sides of the graphite felt with carbon paper, put it into a mold and perform hot pressing curing at a temperature of 100°C for 1h, and obtain a composite bipolar plate after curing.

[0051] Example 6: The composite bipolar plate of this example is prepared by the following steps:

[0052] S1: Dehydrate and deoxygenate the reaction bottle. Under ethylene protection, add 50g of anhydrous chlorobenzene, 6g of methacrylate epoxypropene monomer, and 0.4g of palladium catalyst into the reaction bottle in sequence, stir and dissolve, adjust the ethylene pressure to 0.1MPa, and react at 25°C for 24h. After the reaction is completed, stop the ethylene supply, blow cold wind to remove the anhydrous chlorobenzene, and obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene copolymer containing epoxy groups is obtained;

[0053] S2: 4 g of graphite and 4 g of a hyperbranched polyethylene copolymer containing epoxy groups were added to 750 g of cyclohexanone, and ball-milled for 48 h to obtain a mixed solution. After the mixed solution was centrifuged, the supernatant was filtered to obtain a filter cake, and the filter cake was repeatedly rinsed with cyclohexanone, and then dried to obtain graphene;

[0054] S3: Take 0.75g of graphene, add it to 15g of toluene and ultrasonicate to obtain a dispersion, add the dispersion to 30g of epoxy resin, stir for 2h, ultrasonicate for 2h, then add 30g of curing agent, stir for 30min to obtain a composite liquid;

[0055] S4: Coat the composite liquid onto the surface of 30g of graphite felt, put it into an oven for pre-curing at 60°C for 1h, immerse the graphite felt in the plugging liquid after pre-curing and take it out, cover both sides of the graphite felt with carbon paper, put it into a mold and perform hot pressing curing at a temperature of 100°C for 1h, and obtain a composite bipolar plate after curing.

[0056] Comparative Example 1: The composite bipolar plate of this comparative example was prepared by the following steps:

[0057] S1: Take 30g of epoxy resin, stir for 1h, ultrasonicate for 0.5h, then add 30g of curing agent, stir for 30min to obtain a composite liquid;

[0058] S2: Coat the composite liquid onto the surface of 30g of graphite felt, put it into an oven for pre-curing at 60°C for 1h, immerse the graphite felt in the plugging liquid after pre-curing and take it out, cover carbon paper on both sides of the graphite felt, put it into a mold and perform hot pressing curing at a temperature of 100°C and a time of 0.5h to obtain a composite bipolar plate after curing.

[0059] Comparative Example 2: The composite bipolar plate of this comparative example was prepared by the following steps:

[0060] S1: 4 g of multi-walled carbon nanotubes were added to 750 g of chloroform, and the mixture was ball-milled for 48 h to obtain a mixed solution. After the mixed solution was centrifuged, the supernatant was filtered to obtain a filter cake, and the filter cake was repeatedly rinsed with chloroform, and the carbon nanotubes were obtained after drying;

[0061] S2: Take 3g of carbon nanotubes, add them to 15g of chloroform, and ultrasonicate to obtain a dispersion, add the dispersion to 30g of epoxy resin, stir for 1h, ultrasonicate for 0.5h, then add 30g of curing agent, and stir for 30min to obtain a composite solution;

[0062] S3: Coat the composite liquid onto the surface of 30g of graphite felt, put it into an oven for pre-curing at 60°C for 1h, immerse the graphite felt in the plugging liquid after pre-curing and take it out, cover both sides of the graphite felt with carbon paper, put it into a mold and perform hot pressing curing at a temperature of 100°C and a time of 0.5h to obtain a composite bipolar plate after curing.

[0063] Comparative Example 3: Commercial carbon-plastic composite bipolar plate.

[0064] The composite bipolar plates of the all-vanadium flow battery obtained in Examples 1-6 and Comparative Examples 1-3 were assembled into a battery stack for battery performance testing, and the coulombic efficiency, voltage efficiency and energy efficiency were recorded under the same test conditions. The test results are shown in Table 1:

[0065] Table 1 Summary of battery performance test results

[0066]

[0067] As shown in Table 1 and Figure 2As shown, compared with Comparative Example 3, Examples 1 to 6 have higher voltage efficiency, energy efficiency and tensile strength. Since Examples 1 to 6 of the present invention use the excellent three-dimensional conductive network structure of graphite felt itself as the conductive path, and the graphite felt contains abundant voids, which can be filled into the epoxy resin matrix to form a mechanically enhanced skeleton, the continuity of the conductive path and the mechanically enhanced skeleton is well maintained, thereby improving the conductivity and mechanical strength of the composite bipolar plate at the same time, and improving the voltage efficiency and energy efficiency of the all-vanadium liquid flow battery; Compared with Comparative Example 1, Examples 1 to 6 have higher voltage efficiency and energy efficiency, and the three-dimensional conductive network is further overlapped and improved by introducing nano-carbon materials, so as to further improve the conductive performance of the composite bipolar plate, such as Figure 1 As shown, with the introduction of nano-carbon materials, the resistivity of the composite bipolar plate gradually decreases; compared with Comparative Example 2, Examples 1 to 6 have higher voltage efficiency and energy efficiency, and the nano-carbon material is obtained by auxiliary stripping by introducing a hyperbranched polyethylene copolymer containing an epoxy group at the end. The hyperbranched polyethylene copolymer and the nano-carbon material have a CH-π force, and the nano-carbon material is non-covalently modified to prevent the nano-carbon material from agglomerating. At the same time, the terminal epoxy group can enhance the compatibility of the nano-carbon material with the epoxy resin matrix, improve the dispersion uniformity of the nano-carbon material in the matrix, and improve the conductive performance while maintaining excellent tensile strength.

[0068] From the above detailed description of the embodiments of the present invention, it can be understood that the present invention provides a composite bipolar plate for an all-vanadium liquid flow battery and a preparation method thereof, with epoxy resin as a matrix, graphite felt as a three-dimensional conductive main network, and nano-carbon material as a conductive secondary network to provide more conductive paths for the graphite felt, while introducing a hyperbranched polyethylene copolymer containing an epoxy group at the end to enhance the dispersibility of the nano-carbon material in the epoxy resin, thereby improving the conductivity and mechanical properties of the composite bipolar plate at the same time, and improving the voltage efficiency and energy efficiency of the battery.

[0069] Although the preferred implementation of the present invention has been disclosed as above, it does not limit the present invention. Any technician in this field can make appropriate improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the claims.

Claims

1. A method for preparing a composite bipolar plate for an all-vanadium liquid flow battery, characterized in that: The steps include: Step S1: dehydrating and deoxygenating the reaction bottle, under ethylene protection, sequentially adding 50 parts by mass of anhydrous solvent, 4-6 parts by mass of epoxy-containing acrylic monomer, and 0.2-0.5 parts by mass of palladium catalyst into the reaction bottle, stirring and dissolving, adjusting the ethylene pressure to 0.1-1 MPa, reacting at 25° C. for 12-24 hours, and after the reaction is completed, stopping the ethylene supply, blowing off the anhydrous solvent with cold wind to obtain a saturated preliminary product, and obtaining a hyperbranched polyethylene copolymer containing epoxy groups after separation and purification; the anhydrous solvent comprises at least one of dichloromethane, chloroform, toluene, and chlorobenzene; the epoxy-containing acrylic monomer comprises at least one of 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, glycidyl acrylate, and glycidyl methacrylate; Step S2: adding 2 to 6 parts by mass of carbon material and 1 to 4 parts by mass of hyperbranched polyethylene copolymer containing epoxy groups to 750 parts by mass of solvent, ball milling for 24 to 72 hours to obtain a mixed solution, centrifuging the mixed solution, taking the supernatant and filtering to obtain a filter cake, repeatedly eluting the filter cake with a solvent, and drying to obtain a nano-carbon material; Step S3: taking 0.75-4.5 parts by weight of nanocarbon material, adding it to 15 parts by weight of solvent and ultrasonically obtaining a dispersion, adding the dispersion to 30 parts by weight of epoxy resin, stirring for 1-2 hours, ultrasonically for 0.5-2 hours, then adding 30 parts by weight of curing agent, stirring for 30 minutes to obtain a composite liquid; Step S4: Apply the composite liquid to the surface of 30 parts by mass of graphite felt, put it into an oven for pre-curing, immerse the graphite felt in the plugging liquid after pre-curing and take it out, cover carbon paper on both sides of the graphite felt, put it into a mold and perform hot pressing curing, and obtain a composite bipolar plate after curing.

2. The method for preparing a composite bipolar plate for an all-vanadium liquid flow battery according to claim 1, characterized in that: In step S2, the carbon material includes at least one of graphite and multi-walled carbon nanotubes.

3. The method for preparing a composite bipolar plate for an all-vanadium liquid flow battery according to claim 1, characterized in that: The solvent in steps S2 and S3 includes at least one of chloroform, tetrahydrofuran, N,N-dimethylformamide, cyclohexanone and toluene.

4. The method for preparing a composite bipolar plate for an all-vanadium liquid flow battery according to claim 1, characterized in that: In step S2, the drying temperature is 40-60° C. and the drying time is 6-12 hours.

5. The method for preparing a composite bipolar plate for an all-vanadium redox flow battery according to claim 1, characterized in that: In step S4, the pre-curing temperature is 40-60° C., and the pre-curing time is 1-2 hours.

6. The method for preparing a composite bipolar plate for an all-vanadium redox flow battery according to claim 1, characterized in that: In step S4, the hot pressing temperature is 100-120° C., and the hot pressing time is 0.5-2 h.

7. A composite bipolar plate for an all-vanadium liquid flow battery, characterized in that: The composite bipolar plate is prepared by the method for preparing a composite bipolar plate for an all-vanadium liquid flow battery according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Integrated electrode for vanadium cell and preparation method thereof

    CN103035928A

  • Anti-corrosion industrial coating and preparation method thereof

    CN114426793A